AGE, GENDER AND GRADE EFFECT ON FOREIGN LANGUAGE ANXIETY AMONG CHILDREN - Aydin, Selami; Harputlu, Leyla; CÌ§elik, SÌ§eyda Savran; UsÌ§tuk, OÌˆzgehan; GuÌˆzel, Serhat (TEFLIN Journal, 2017)
The number of studies on the relationship between certain demo- graphic variables, age, gender and grade, and the levels of foreign language anxiety (FLA) in the English as a foreign language (EFL) context regarding adult and young learners is fairly limited, whereas the findings obtained from prior studies did not reach a consensus on the influences of FLA, and studies mainly focused on adult language learners rather than young learners. This study aims to explore the effect of age, gender and grade differences on FLA and its types, communication apprehension, fear of negative evaluation and test anxiety, among Turkish children who learn English as a foreign language. The participants were 494 children enrolled at primary and secondary schools. The data collection tools were a background questionnaire interrogating the variables mentioned and the Children’s Foreign Language Anxiety Scale (CFLAS). After computing the reliability coefficient of the scale and total variance, independent samples t-test and ANOVA were used to see the relationships between the levels of FLA and its types and subject variables, age, gender, and grade. The results showed that age, gender, and grade constitute significant differences regarding FLA and its types, when several items in the CFLAS were considered. In the light of findings, several practical recommendations are listed.